Automated Testing of Ticket Booking Application Using Selenium and ML. - Dammalapati, Komali; Krishna, Kolla Mohan; Prabha, B.; Irfan, Patan; Katumala, Ratnakar; Vamsi, Sampathi; Sasank, V. V. S. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Tests are conducted to locate or detect device failures and defects. What test cases are only evaluated in automated testing. It's not just to test new connections or stuff but it can be appreciated from previous experiences that we are doing something new here to try and use the experience to get new results. The layout of a web scraper, computer training (ML), and selenium are three strata to accomplish this approach. It will be checked on the web page and trained on a framework based on a human understanding to understand what test cases should be followed for every single feature of the webpage and system next time on station, based on that info on the website, to conduct health tests and smoke tests intelligently. The system learns what to do with a web feature such as a button. The outputs that can be obtained even by classifying the form of output are error pages or are not intended for the page. This strategy allows thewider business organization, instead of carrying out human activities, to comply with an innovative challenge inresearch.